PERSON-ORGANIZATION FIT DALAM RANTAI DISTRIBUSI PEMASARAN - Abdul Haeba Ramli (Jurnal Manajemen dan Pemasaran Jasa, 2019)
AbstractEmployee turnover in the poultry distribution company in Jakarta indicates low person-organization fit, organizational commitment and high turnover intention. The purpose of this study is to determine the effect of person-organization fit and organizational commitment on turnover intention. Quantitative methods are used in this study. The population for this research is the employees of a chicken distribution company in Jakarta with more than 2.000 people. The sampling technique used is purposive sampling with the number of samples of 128 peoples. Data collection technique uses questionnaires and regression analysis. Finding on the research results shows that there is positive and significant influence of person-organization fiton organizational commitment and negative and significant influence of person-organization fit on turnover intention, and also the influence of person-organization fit and organizational commitment on turnover intention.